Current status of Remittance and Nepalese Economy - Ghimire, Shankar (Jana Adarsha Research Journal, 2025)
This article explores the current trends of remittance in Nepal and its relationship with economic growth during the period of three and half decades till 2021/22. The recent remittance utilization pattern reflects that 58.78 percent of the money earned from foreign employment is spent on daily consumption, 22.48 percent on education and health, 10.07 percent on debt repayment and 8.67 percent on entertainment. The result shows that mere increasing remittance income does not support for the economic growth and development of the nation unless it is extensively used into the productive sectors. The Nepalese economy is gradually becoming consumption oriented due to remittance income that naturally leads to dependency resulting in the dearth of resource for investment. Thus, it is recommended to the government agencies for the formulation and implementation of remittance utilization policy for the enhancement of national economy.